Development Of Interactive Media For A Virtual Laboratory On Chemical Equilibrium Using Articulate Storyline 3 - Purba, Yenni Sofia; Pane, Agil Makarim; Zalukhu, Fandel Affection Christensen; Andini, Rizky; Wulandari, Indah Putri; Fitri, Annisa; Muchtar, Zainuddin (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
This research aims to develop an interactive media Virtual Laboratory on the topic of chemical equilibrium. This research was conducted at SMA Negeri 1 Galang. This type of research uses the development method (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation, but this research is limited to the development stage. This research uses a sample of 28 students in 1 class, 1 chemistry teacher, and 2 expert validators. Data collection in this study was conducted through interviews and questionnaires. The validation results by media experts indicate that this virtual laboratory is valid with an average feasibility percentage of 84.71%, while validation by content experts obtained a percentage of 90%. Teacher responses indicate validity with an average of 95.55%, and student responses provide an average of 96.45%, all of which fall into the "very feasible" category.Keywords: : Virtual Laboratory, Chemical Equilibrium, Articulate Storyline 3, Development, Interactive MediaDOI: 10.23960/jppk.v13.i3.32285